2010
DOI: 10.1073/pnas.0914826107
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the right temporoparietal junction with transcranial magnetic stimulation reduces the role of beliefs in moral judgments

Abstract: When we judge an action as morally right or wrong, we rely on our capacity to infer the actor's mental states (e.g., beliefs, intentions). Here, we test the hypothesis that the right temporoparietal junction (RTPJ), an area involved in mental state reasoning, is necessary for making moral judgments. In two experiments, we used transcranial magnetic stimulation (TMS) to disrupt neural activity in the RTPJ transiently before moral judgment (experiment 1, offline stimulation) and during moral judgment (experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
400
5
16

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 504 publications
(464 citation statements)
references
References 53 publications
(70 reference statements)
32
400
5
16
Order By: Relevance
“…Developmental studies have shown that children's motive-based moral reasoning was positively correlated with their false-belief understanding, suggesting a relation between children's theory of mind and the domain of moral judgment (Baird & Astington, 2004). This close connection between moral judgment and ToM is further supported by recent neuroimaging evidence (Young, Camprodon, Hauser, Pascual-Leone, & Saxe, 2010;Young, Cushman, Hauser, & Saxe, 2007). Moral judgments require that participants balance evaluations of the actual outcomes against considerations of the agent's desires, beliefs and intention, which rely upon ToM reasoning.…”
Section: Introductionmentioning
confidence: 90%
“…Developmental studies have shown that children's motive-based moral reasoning was positively correlated with their false-belief understanding, suggesting a relation between children's theory of mind and the domain of moral judgment (Baird & Astington, 2004). This close connection between moral judgment and ToM is further supported by recent neuroimaging evidence (Young, Camprodon, Hauser, Pascual-Leone, & Saxe, 2010;Young, Cushman, Hauser, & Saxe, 2007). Moral judgments require that participants balance evaluations of the actual outcomes against considerations of the agent's desires, beliefs and intention, which rely upon ToM reasoning.…”
Section: Introductionmentioning
confidence: 90%
“…To agree with subjective claims, it is assumed that participants must hold on to some mental state representation (either their own or others', see Saxe, 2009). Haxby, 2007;Ruby & Decety, 2003;Saxe & Kanwisher 2003;Saxe & Powell, 2006;Vogeley et al, 2001;Young et al, 2010;Young, Cushman, Hauser, & Saxe, 2007;Young, Scholz & Saxe, 2011;Young & Saxe, 2008;2009). Some ToM ROIs, such as RTPJ, have been shown to play a critical role in moral judgment (Young et al, 2010;Young & Saxe, 2009); however, researchers have hypothesized that these regions are critical to processes underlying moral judgment (e.g.…”
Section: Metaethics and Mental State Representationsmentioning
confidence: 99%
“…By contrast, objective claims are mind-independent (e.g. "2 + 2 = 4" is true, regardless of what anyone believes; Goodwin & Darley, 2010;Sayre-McCord, 1986 What this all means for moral claims, is that if morals are represented as subjective, then they should elicit greater activity in brain regions responsible for mental state representation.This hypothesis is made testable by recent work in social neuroscience: a set of brain regionsthe Theory of Mind (ToM) network-has been consistently implicated in mental state representation (Amodio & Frith, 2006;Decety & Cacioppo, 2012;Saxe & Kanwisher, 2003;Young, Camprodon, Hauser, Pascual-Leone, & Saxe, 2010;Young & Saxe, 2009; for reviews see Schurz et al, 2014; Van Overwalle, 2009). Within this network, some regions of interest (ROIs) are more active during tasks that involve general forms of social cognition, such as trait inference, or assessing the similarity of others to the self (dorsal/ventral-medial prefrontal cortex; DMPFC, VMPFC; Amodio & Frith, 2006;Decety & Cacioppo, 2012;Harris, Todorov, & Fiske, 2005; Jenkins & Mitchell, 2010;Ma, Vandekerckhove, Van Hoeck, & Van Overwalle, 2012;Mitchell, Banaji, & Macrae, 2005;Ochsner et al, 2005;Schurz et al, 2014; Van Overwalle, 2009;Young & Saxe, 2009).…”
mentioning
confidence: 99%
“…Convergent TMS evidence suggests that temporarily disrupting RTPJ activity using online and offline TMS has the most pronounced effect on moral judgments of attempted harms as well, biasing participants to judge attempted harms more leniently, based on the neutral outcome, rather than the negative intent (Young, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The critical role of these brain regions, including the RTPJ, for evaluating harmful actions has also been the topic of recent research, using transcranial magnetic stimulation (TMS) (Young, Camprodon, Hauser, Pascual-Leone, & Saxe, 2010) and fMRI . For example, the same regions for theory of mind in non-moral contexts were recruited when participants read explicit statements of agents' beliefs about whether or not they would cause harm (e.g.…”
Section: Introductionmentioning
confidence: 99%